Faktor Sosial Penyebab Tindak Pidana Pencurian dalam Perspektif KUHP Baru UU No. 1 Tahun 2023 - syafii, Arimas Kuntoro; Satria Nur Ramadhana; Hestu Pawestri; Anggita Rohmanika; Sukron Abdul Kadir (Cattleya Darmaya Fortuna, 2026)
This study aims to examine the social factors causing theft as a criminal act from the perspective of legal sociology based on Law Number 1 of 2023 on the Criminal Code. The method employed is normative legal research using a legal literature review approach that integrates statutory, conceptual, and historical approaches. Legal materials consisting of primary, secondary, and tertiary sources were collected through systematic library research and analyzed qualitatively using prescriptive, comparative, systematic, and sociological-juridical analysis. The findings indicate that theft is a multidimensional social phenomenon driven by structural poverty, unemployment, weakening social control, and a socially permissive environment toward deviant behavior. Sociological analysis using strain theory, social control theory, anomie theory, and labeling theory demonstrates that theft is a product of complex interactions between individuals and unjust social structures. The National Criminal Code under Law No. 1 of 2023 introduces significant reforms through a more humane, proportional, and restorative justice-oriented approach to punishment, reflecting legislative awareness that criminal law enforcement must be responsive to social realities. The implications of legal sociology demand a transformation in law enforcement from a purely punitive paradigm toward an integrative paradigm that sustainably and justly addresses the structural roots of crime..